Association between person‐centered maternity care and newborn complications in Kenya. Issue 1 (9th October 2019) - Sudhinaraset, May; Landrian, Amanda; Afulani, Patience A.; Diamond‐Smith, Nadia; Golub, Ginger
Abstract: Objective: Despite the recognized importance of person‐centered care, very little information exists on how person‐centered maternity care (PCMC) impacts newborn health. Methods: Baseline and follow‐up data were collected from women who delivered in government health facilities in Nairobi and Kiambu counties in Kenya between August 2016 and February 2017. The final analytic sample included 413 respondents who completed the baseline survey and at least one follow‐up survey at 2, 6, 8, and/or 10 weeks. Data were analyzed using descriptive, bivariate, and multivariate statistics. Logistic regression was used to assess the relationship between PCMC scores and outcomes of interest. Results: In multivariate analyses, women with high PCMC scores were significantly less likely to report newborn complications than women with low PCMC scores (adjusted odds ratio [aOR] 0.39, 95% confidence interval [CI] 0.16–0.98). Women reporting high PCMC scores also had significantly higher odds of reporting a willingness to return to the facility for their next delivery than women with low PCMC score (aOR 12.72, 95% CI 2.26–71.63). The domains of Respect/Dignity and Supportive Care were associated with fewer newborn complications and willingness to return to a facility. Conclusion: PCMC could improve not just the experience of the mother during childbirth, but also the health of her newborn and future health‐seeking behavior. Abstract : Higher person‐centered maternity care is associated with lower levels of reported newborn complications and higher levels of willingness to return to the health facility.